Relational Processes in Mandalika’s Tourism Texts: A Systemic Functional Linguistic Analysis - Silalahi, Elisa Debora; Sujatna, Eva Tuckyta Sari; Krisnawati, Ekaning (NOBEL: Journal of Literature and Language Teaching, 2024)
Mandalika is an Indonesian tourist destination notable for sports tourism, as a result of the construction of the Mandalika circuit as an infrastructure for various international events to be held. Moreover, Mandalika also contains natural and cultural resources that can be explored. Therefore, it is categorized as one of the 5 Super Priority Destinations and is still being developed to attract domestic and international visitors. This research analyses relational processes found in five selected Mandalika tourism texts uploaded on the Indonesian Ministry of Tourism and Creative Economy website under the Systemic Functional Linguistics point of view. Based on the data acquired in this study, a qualitative method is used. Based on the analysis, each clause broadly reflects Mandalika’s features, but the participants involved have different ways of describing each feature. In addition, the dominance of identifying relational processes in intensive clauses (33%) highlights the most prominent elements of Mandalika, providing readers with the greatest recommendations to enjoy throughout their vacation to Mandalika.